Формування людини нового типу та трансформація релігійності в інформаційному суспільстві - Дарморіз, Оксана (Lviv Polytechnic Publishing House, 2016)
Проаналізовано феномен Інтернету як один із головних засобів масової комунікації в сучасному світі. Визначено його сутнісні характеристики та окреслено вплив на формування людської особистості та спільноти. Розглянуто віртуальну реальність як новий соціокультурний простір та чинник трансформації релігійності та особистісних якостей сучасної людини. З’ясовано її головні риси та способи комунікації у віртуальному світі. Виявлено особливості існування людини та релігії в мережевій спільноті. The article analyses religion of a modern person, considering the role of the Internet and virtual reality in the information society. Modern society is an open information society in which the main role in economic, political and cultural development is information. There can be distinguished the following features of Information Society: fast growing of electronic information resources, free dissemination of information and free access to it. A person in the modern world has to instantly react on emergence of available information calls, technical innovations, rapid social and cultural development. Religion uses new means of communication for their own distribution and better communication with their followers or possible adepts. The Internet is increasingly becoming a mediator between a person and religion where everyone can get information about variety of religions, practice them and communicate with other believers. At the modern stage, a person departs from established forms of communication with the supernatural and begins to create new forms of religiosity which are a better reflection of the current state of social and scientific development. Traditional religions use the Internet for communication with their followers. Besides, new religions - cyber religions - appear. Cyber religions radically change human consciousness since real communication with the supernatural strength is replaced by the virtual, unreal, and thus, formed ideas are not about true communion with God but about a game which can stop at any time or start again. Moreover, a person usually acquires new features which are not real but which he or she wants to receive. He or she turns to the Creator with help of the new technology, creates an alternative world in virtual reality and receives unlimited power over him.
Formation of newtype of human and transformation of religiosity in the information society
Keywords: релігійність; релігія; Інтернет; віртуальна реальність; нові медіа; інформація; людина; суспільство; religious; religion; the Internet; virtual reality; new media; information; person; society; 316.752:2]-044.922:[316.42:004]